Designing a future value stream mapping to reduce lead time using SMED-A case study - Amir, Azizi; Manoharan, Thulasi (Elsevier Ltd, 2015)
Many manufacturers struggle with improving productivity, producing the right products or services at the right place and meeting on-time delivery. To survive in today`s era competitive world, manufacturers need to find new ways to reduce the manufacturing lead times in order to improve productivity and operating principle. Nowadays, it is targeted to improve the productivity performance by reducing the production lead time and production waste that are the most important goals for almost all manufacturing companies. The main objective of this study is to design an efficient Value Stream Mapping (VSM) to improve the productivity in Small Medium Enterprise (SME) by eliminating non-value added activities. The methodology of the study is to firstly analyze the production waste in current state map, secondly to use the Kaizen activity with Single Minute Exchange of Die (SMED) to effectively support future state for process improvement of the action plan. As a conclusion, this paper presents that the designed Future Value Stream Map (FVSM) helps to effectively identify wasteful activities and production processes. VSM and Kaizen serve as an input for continuous improvement by reducing the manufacturing lead time using SMED in SME.